The use of ERACS method for accelerating conscious recovery time in cesarean section patients - Andrifan, Andrifan; Wahyuningtyas, Eka Sakti; Masithoh, Robiul Fitri; Priyo, Priyo (Universitas Aisyiyah Yogyakarta, 2024)
Enhanced Recovery After Caesarean Section (ERACS) is a method that is currently being widely developed, one of which is for mothers undergoing cesarean sections. The use of ERACS enables postpartum recovery time to be faster, thus improving mobility, accelerating labor recovery, and providing other benefits such as enhancing the quality of care and reducing the use of consumables. However, not all mothers and hospitals use ERACS. The purpose of this study is to determine the difference in conscious recovery time in the recovery room between patients post-surgery using the ERACS method and the conventional method at RSUD Soerojo. This comparative study uses a quantitative approach, quasi-experimental, with a control group design. The population includes all post-cesarean section patients using spinal anesthesia, with the sample being post-cesarean section patients using ERACS and the conventional method. There is a significant difference between spinal anesthesia techniques with ERACS and the conventional method in terms of accelerating the recovery time of post-cesarean section patients in the recovery room, with a significance value of 0.000. The use of ERACS should be considered for all mothers undergoing cesarean sections in all hospitals if there are no contraindications